The use of Blockchain and its possibilities to the informational flow of supply chains - Moreira, Fábio Mosso (2019)
The aim is to identify the possibilities of using Blockchain as a model to support the infrastructure of data and information transactions in a supply chain, listing its potential applications for this informational flow. For that, a theoretical revision was performed in scientific articles retrieved in the SCOPUS Elsevier and IEEE Xplore knowledge bases. The analysis of the theoretical corpus was carried out by the application of the Content Analysis method, using the categorical analysis type. The results of the research present six categories to represent the possibilities of using Blockchain in the studied context: (i) Traceability of the data; (ii) Data integrity; (iii) Data audit and transparency; (iv) Reduction of information losses; (v) Interoperability with Internet of Things devices and other systems, and; (vi) Standardization of digital representations.